MiR‐375 is Essential for Human Spinal Motor Neuron Development and May Be Involved in Motor Neuron Degeneration. (20th November 2015) - Bhinge, Akshay; Namboori, Seema C.; Bithell, Angela; Soldati, Chiara; Buckley, Noel J.; Stanton, Lawrence W.
Abstract: The transcription factor REST is a key suppressor of neuronal genes in non‐neuronal tissues. REST has been shown to suppress proneuronal microRNAs in neural progenitors indicating that REST‐mediated neurogenic suppression may act in part via microRNAs. We used neural differentiation of Rest ‐null mouse ESC to identify dozens of microRNAs regulated by REST during neural development. One of the identified microRNAs, miR‐375, was upregulated during human spinal motor neuron development. We found that miR‐375 facilitates spinal motor neurogenesis by targeting the cyclin kinase CCND2 and the transcription factor PAX6. Additionally, miR‐375 inhibits the tumor suppressor p53 and protects neurons from apoptosis in response to DNA damage. Interestingly, motor neurons derived from a spinal muscular atrophy patient displayed depressed miR‐375 expression and elevated p53 protein levels. Importantly, SMA motor neurons were significantly more susceptible to DNA damage induced apoptosis suggesting that miR‐375 may play a protective role in motor neurons. Stem Cells 2016;34:124–134